Remote health monitoring system in a rural population: Challenges and opportunities - Jacey-Lynn, Minoi; Wee, Alvin Yeo (2015)
This paper discusses remote health monitoring as a potential application field in telecentres at rural areas. We present the challenges faced and opportunities with emphasis on patients with hypertension using a remote health monitoring system. We will also discuss the potential of deploying mHealth applications as a value added to the telecentres. The remote blood pressure health monitoring system will read, store and send data over wireless network to a remote server. Medical doctors can view the data on a regular basis remotely from a website. This community-based participatory research study carried out BP monitoring on residents from a rural village in Sarawak, Borneo and did follow-up assessments on the available health care for them. Structured quantitative and qualitative research tools were carried out on a wide range of clients – the patients, telecentre managers and medical doctors. Structured and semi-structured data collection techniques, such as questionnaires, group discussions and interviews were gathered. Observation of the whole process of interaction between the patients with the managers was also captured. The aim of the project is to determine the degree to which remote health monitoring interventions can be integrated to telecentres in rural areas to increase awareness in healthy living and wellness.